2008
DOI: 10.1007/s00436-008-0974-8
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant and larvicidal effects of plant extracts against Spodoptera litura (F.), Aedes aegypti L. and Culex quinquefasciatus Say

Abstract: A screening for larvicidal activity of plant extracts with some known medicinal attributes could lead to the discovery of new agents for pest and vector control. In the backdrop of recent revival of interest in developing plant-based insecticides, the present study was carried out to evaluate the larvicidal properties in three medicinal plants growing abundantly in the region of Chitheri Hills, Dharmapuri District, India. Antifeedant and larvicidal activity of the acetone, chloroform, ethyl acetate, hexane and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 36 publications
4
52
0
1
Order By: Relevance
“…Finally, the crude extract appeared less toxic than O. canum and R. nasutus methanol extract (LC 50 ϭ36 and 68 ppm, respectively). 21) In addition, the dipping method showed higher toxicity than the sprayer method with a significant difference (Pϭ0.0006 and 0.0024 at PϽ0.05 for 24 and 48 hr after exposed) according to Duncan's New Multiple's Range Test 22) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the crude extract appeared less toxic than O. canum and R. nasutus methanol extract (LC 50 ϭ36 and 68 ppm, respectively). 21) In addition, the dipping method showed higher toxicity than the sprayer method with a significant difference (Pϭ0.0006 and 0.0024 at PϽ0.05 for 24 and 48 hr after exposed) according to Duncan's New Multiple's Range Test 22) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The sublethal effects of chemical compounds on natural specimens of A. aegypti were investigated by Shaalan 27 who evaluated the effect of synthetic insecticides and Callitris glaucophyllam extracts and various chemical insecticides Adanan et al 28 and Kamaraj 29 showed that, while not fatal, these sublethal concentrations lead to a disorder in insect biology, both morphologically and physiologically, interfering with the duration of the larval period and the pupae exposed to these concentrations, refl ected in the emergence of adults.…”
Section: Discussionmentioning
confidence: 99%
“…Plant derived pesticides provide a more natural, "environmentally friendly" approach to pest control than synthetic insecticides. Extensive surveys and reports on plants used as insecticides can be found in the literature [2,3] .…”
Section: Introductionmentioning
confidence: 99%